Decentralized Adaptive Double Integral Sliding Mode Controller for Multi-Area Power Systems. (8th October 2018) - Le Ngoc Minh, Bui; Huynh, Van Van; Nguyen, Tam Minh; Tsai, Yao Wen
Abstract : Most of the existing results for load frequency control of multi-area interconnected power systems can only be obtained when the norm of the aggregated uncertainties is bounded by a positive constant. This condition is difficult to achieve in real multi-area interconnected power systems. In this paper, a new load frequency control (LFC) for multi-area interconnected power systems is developed based on a decentralised adaptive double integral sliding mode control technique where the above limitation is eliminated. First, an adaptive gain tuning law is adopted to estimate the unknown upper bound of the aggregated uncertainties. Second, a double integral sliding surface based adaptive sliding mode controller is proposed to improve the transient performance of the closed loop system. Simulation results show that the proposed control law results in shortening the frequency's transient response, avoiding the overshoot, rejecting disturbance better, maintaining required control quality in the wider operating range, and being more robust to uncertainties as compared to some existing control methods.